Binary composites of sonochemically synthesized cobalt phosphates/polyaniline for supercapattery devices. (October 2021) - Alam, Faiz; Iqbal, Muhammad Zahir; Alam, Shahid; Alhassan, Najam
Highlights: Green synthesis of (Co3 (PO4 )2 -PANI) based binary composites in different aspect ratios. Electrochemical performance of as synthesized nanomaterials was investigated in three electrode assembly. Supercapattery device is fabricated comprises of (Co3 )0.70 (PO4 )2 -PANI0.30 . The device exhibits an outstanding specific energy of 53.2 Whkg −1 with a maximum specific power of 6027 Wkg −1, along with excellent cyclic stability of 99% after 3000 cycles. On the bases of Dunn's model the capacitive and diffusion-controlled contribution in a supercapattery device is evaluated. Abstract: This work focuses on enhancing the electrochemical performance of cobalt phosphate (Co3 (PO4 )2 ) via polyaniline (PANI) for high performance hybrid energy storage devices also termed as supercapattery. For projected drive binary composites cobalt phosphate and PANI at different Wt% were made and composition of PANI was optimized. The composition reveals prime electrochemical performance possessing a maximum specific capacity of 638 C/g while operating at 0.8 A/g in three electrode assembly. The charge storage performance was further scrutinized in two electrode assembly, a supercapattery device is fabricated by coupling Co0.70 (PO4 )2 /PANI0.30 (S3) (positive) and activated carbon (negative) electrodes. The developed device exhibits exceptional energy storage performance with an ultrahigh specific energy (ES ) of 53.2 Wh/kg along with a specific power (PS ) of 432 W/kg at 0.5 A/g. The maximum specific power delivered by assembled supercapattery device is 6027 W/kg in parallel with an specific energy of 7.1 Wh/kg. The supercapattery device also demonstrates an outstanding cyclic stability potential of 97.6% and excellent columbic efficiency of 87% after 5000 continuous charge/discharge cycles. Furthermore, the Dunn's model is employed to calculate the capacitive and diffusive impact in total capacity of the device. The outstanding performance of the developed binary composites compared with previously reported literature, provides an efficient and preferable electrode material for potential applications in high-performance energy storage technologies. Graphical abstract: Image, graphical abstract